O ensino de tarefas para crianças com diagnóstico de autismo: comparação da eficácia de três procedimentos - Marques, Fernanda Cristina (2013)
This study evaluated three procedures to teach single digit addition to three children diagnosed with Autism. It was intended to specifically compare a parallel design of independent variables for the three procedures including Constant Time Delay, Simultaneous Prompting and No-No Prompting. With the simultaneous model, a matching procedure was used to train the children to point to the sum (model) when given a field of three numbers to compare, one being the correct answer. Prior to teaching, a complete probe of all additions of all blocks was implemented to determine baseline levels. Then the children were taught three additions in each block for each procedure, ensuring that the number of training trials for all teaching sessions remained constant for each procedure in each session. Daily probes were also conducted, as they were considered the most effective to achieve 100% accuracy in three consecutive daily sessions. Results indicate that the Constant Time Delay procedure was the most effective for teaching two participants whereas Simultaneous Prompting was most effective for the other participant. Theses results also demonstrate the need for more comparative studies to further evaluate the optimal teaching procedure